2017
DOI: 10.5380/rsa.v18i4.51205
|View full text |Cite
|
Sign up to set email alerts
|

Utilização De Nitrogênio E Enxofre Em Cobertura No Feijão Preto Safrinha

Abstract: Resumo: Cultivado em diferentes sistemas de produção, com um ciclo inferior a 100 dias, o feijão é uma ótima opção para a safrinha na região Sul do Brasil. Contudo a recomendação para adubação de lavouras altamente tecnificadas ainda é um desafio. O objetivo deste trabalho foi avaliar a utilização de nitrogênio e enxofre aplicado em cobertura na cultura do feijoeiro. Para isso foi implantado um experimento a campo na safrinha de 2016 na cidade de Chapecó -SC. O delineamento experimental foi de blocos ao acaso … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The fact that nitrogen did not affect the mass of 100 grains was also verified by Kolling and Ozelame (2017), who, using doses of 0 kg ha -1 , 25 kg ha -1 , 50 kg ha -1 , and 75 kg ha -1 of nitrogen, found no effect on seed mass. Other authors also found no differences in the effect of the nitrogen dose on the mass of 100 grains, such as Moreira et al (2013); Guimarães et al (2017), and Sabundijian et al (2016).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The fact that nitrogen did not affect the mass of 100 grains was also verified by Kolling and Ozelame (2017), who, using doses of 0 kg ha -1 , 25 kg ha -1 , 50 kg ha -1 , and 75 kg ha -1 of nitrogen, found no effect on seed mass. Other authors also found no differences in the effect of the nitrogen dose on the mass of 100 grains, such as Moreira et al (2013); Guimarães et al (2017), and Sabundijian et al (2016).…”
Section: Resultsmentioning
confidence: 55%
“…Some authors, such as Guimarães et al (2017) and Sabundijian (2013), found no statistical differences in nitrogen doses for bean grain yield. Kolling and Ozelame (2017) found that for every 10 kg of nitrogen applied; there was an increase in crop productivity of 14 kg ha -1 . Amaral et al (2016), in an experiment conducted in the city of Jaboticabal, SP, evaluated five doses of nitrogen (0 kg ha -1 , 40 kg ha -1 , 80 kg ha -1 , 120 kg ha -1 , and 160 kg ha -1 ) and observed that the doses influenced bean grain yield, in which the application of 136 kg ha -1 provided 2565 kg ha -1 of productivity.…”
Section: Resultsmentioning
confidence: 97%
“…The authors also concluded that genetic variability makes it possible to select more efficient cultivars for cultivation under conditions of low sulfur availability. Kolling and Ozelame (2017), when studying different combinations of nitrogen and sulfur dozen in off-season black beans, found that the combined use of nitrogen and sulfur resulted in higher grain yield, a higher number of grains per pod and longer pod length, increasing the yield of these components, in addition to the higher yield of grains per area. Pereira et al (2021), when studying the application of different sulfur dozens in the BRS Guariba and BRS Tumucumaque cowpea varieties under optimal irrigation conditions, found that the vegetative characteristics of these varieties were not influenced by the treatments, and the nutrient content available in the soil (32 mg dm-3) was sufficient for normal plant development.…”
Section: Resultsmentioning
confidence: 99%